Physical Changes in World Heritage Sites under the Pressure of Tourism: The Case of Cumal?k?z?k Village in Bursa - Bilgin, Elif Acar; Arslan, Tülin Vural; Durak, Selen (European Journal of Sustainable Development, 2019)
Bursa, the first capital city of Ottoman Empire, was inscribed into UNESCO World Heritage List in 2014 with Khans Area, Sultan Complexes (Kulliyes) and Cumal?k?z?k village representing the relationship between urban and rural areas of Early Ottoman Period. Cumal?k?z?k Village is one of the most popular rural settlements in Bursa which maintains its urban fabric, road pattern, and traditional houses. Under the pressure of increasing tourism, traditional houses began to be used for commercial purposes with the interventions made by their owners which threatens the sustainability and preservation of their authenticity and integrity. This paper aims to determine the interventions in historic dwellings and courtyards due to tourism. For this purpose, three historic houses on the most visited sightseeing route starting from the village square, continuing along the nodes of the settlement following the mosque and the hammam (public bath) to examine the physical changes under the effect of tourism. Keywords: cultural tourism; rural heritage; world heritage sites; Cumal?k?z?k; Bursa